Triassic Foraminifera from the Great Bank of Guizhou, Nanpanjiang Basin, south China: taxonomic account, biostratigraphy, and implications for recovery from end-Permian mass extinction. (December 2021) - Altıner, Demir; Payne, Jonathan L.; Lehrmann, Daniel J.; Özkan-Altıner, Sevinç; Kelley, Brian M.; Summers, Mindi M.; Yu, Meiyi
Abstract: Foraminifera are important components of tropical marine benthic ecosystems and their recovery pattern from the end-Permian mass extinction can yield insights into the Mesozoic history of this group. Here we report the calcareous and agglutinated foraminifera recovered from five measured stratigraphic sections on the Great Bank of Guizhou, an uppermost Permian to Upper Triassic isolated carbonate platform in the Nanpanjiang Basin, south China. The material contains >100 Triassic species, including three that are newly described ( Arenovidalina weii n. sp., Meandrospira ? enosi n. sp., and Spinoendotebanella lehrmanni n. gen., n. sp.), ranging from Griesbachian (Induan) to Cordevolian (Carnian) age. The species belong to the classes Miliolata, Textulariata, Fusulinata, Nodosariata, and to an unknown class housing all aragonitic forms of the orders Involutinida and Robertinida. Based on previously established conodont zones and carbon isotope chemostratigraphy, the Griesbachian (early Induan) through Illyrian (late Anisian) interval has been subdivided into 12 foraminiferal zones and two unnamed intervals devoid of foraminifera. Following the extinction at the Permian-Triassic boundary, habitable ecological niches of Griesbachian age were invaded by disaster taxa that subsequently became extinct during the Dienerian (late Induan) and left no younger descendants. The disaster taxa were replaced by Lazarus taxa with Permian origins, which were then decimated by the Smithian-Spathian (mid-Olenekian) boundary crisis. The tempo of recovery appears to have been modulated by environmental changes during the Griesbachian through Smithian that involved both climate change and expansion of anoxic ocean bottom waters. Uninterrupted and lasting recovery of benthic foraminifera did not begin until the Spathian. UUID: http://zoobank.org/2a6e9061-b163-402a-9098-8765a80576b3